The Intensification Of Islamic Proselytization Through Maritime Trade In Aceh Darussalam Sultanate, 1607-1675 CE - Fadhilah Ariani; Sujadi (Fakultas Adab dan Ilmu Budaya UIN Sunan Kalijaga Yogyakarta, 2026)
Abstract: The majority of maritime trade activities emphasize profit as the primary goal; however, in the Sultanate of Aceh Darussalam, maritime trade was not solely profit-oriented but also utilized as a means of Islamic propagation. This study examines the role of maritime trade in the Sultanate of Aceh Darussalam (1607–1675 CE) in intensifying Islamic proselytization in Southeast Asia. The research highlights how maritime trade, typically viewed through an economic lens, also served as a strategic instrument for religious dissemination. The Sultanate utilized revenues from trade, including customs duties and zakat, to fund the construction of mosques, establish Islamic educational institutions, and disseminate religious literature. Moreover, Aceh served as a transit hub for pilgrims on their way to Mecca, facilitating scholarly exchanges and strengthening Islamic networks across the archipelago. Employing a historical methodology with an economic sociology approach, this study integrates the economic and religious dimensions of Aceh’s maritime activities. The findings underscore the Sultanate’s dual function as a cosmopolitan trade center and a bastion of Islamic education, offering a fresh perspective on the interconnectedness of commerce and religion in Nusantara historiography. Keywords: maritime trade; Sultanate of Aceh Darussalam; Islamic proselytization Abstrak: Mayoritas kegiatan perdagangan maritim menekankan pada profit sebagai tujuan yang ingin dicapai, namun di Kesultanan Aceh Darussalam perdagangan maritim tidak hanya mementingkan profit namun juga dimanfaatkan untuk dakwah Islam. Penelitian ini mengkaji peran perdagangan maritim di Kesultanan Aceh Darussalam (1607-1675 M) dalam mengintensifkan dakwah Islam di Asia Tenggara. Penelitian ini menyoroti bagaimana perdagangan maritim, yang biasanya dilihat dari sudut pandang ekonomi, juga berfungsi sebagai instrumen strategis untuk penyebaran Islam. Kesultanan Aceh memanfaatkan pendapatan dari perdagangan, seperti bea cukai hingga zakat, untuk mendanai pembangunan masjid, mendirikan lembaga pendidikan Islam, dan menyebarkan literatur keagamaan. Selain itu, Aceh berfungsi sebagai pusat transit bagi para jamaah haji yang akan menuju Mekkah, memfasilitasi pertukaran keilmuan dan memperkuat jaringan Islam di seluruh nusantara. Dengan menggunakan metodologi sejarah dengan pendekatan sosiologi ekonomi, penelitian ini mengintegrasikan dimensi ekonomi dan agama dalam kegiatan maritim Aceh. Hasil penelitian ini menggarisbawahi fungsi ganda Kesultanan Aceh sebagai pusat perdagangan kosmopolitan dan pusat pendidikan Islam, yang menawarkan perspektif baru mengenai keterkaitan antara perdagangan dan agama dalam historiografi Nusantara. Kata Kunci: perdagangan maritime; Kesultanan Aceh Darussalam; dakwah Islam